Human mesenchymal stem cells from the umbilical cord matrix: Successful isolation and ex vivo expansion using serum‐/xeno‐free culture media. Issue 4 (7th March 2013) - Simões, Irina N.; Boura, Joana S.; dos Santos, Francisco; Andrade, Pedro Z.; Cardoso, Carla M. P.; Gimble, Jeffrey M.; da Silva, Cláudia L.; Cabral, Joaquim M. S.
Abstract Mesenchymal stem cells (MSC) could potentially be applied in therapeutic settings due to their multilineage differentiation ability, immunomodulatory properties, as well as their trophic activity. The umbilical cord matrix (UCM) represents a promising source of MSC for biomedical applications. The number of cells isloated per umbilical cord (UC) unit is limited and ex vivo expansion is imperative in order to reach clinically meaningful cell numbers. The limitations of poorly defined reagents (e.g. fetal bovine serum, which is commonly used as a supplement for human MSC expansion) make the use of serum‐/xeno‐free conditions mandatory. We demonstrated the feasibility of isolating UCM‐MSC by plastic adherence using serum‐/xeno‐free culture medium following enzymatic digestion of UCs, with a 100% success rate. 2.6 ± 0.21 × 105 cells were isolated per UC unit, of which 1.9 ± 0.21 × 105 were MSC‐like cells expressing CD73, CD90, and CD105. When compared to adult sources (bone marrow‐derived MSC and adipose‐derived stem/stromal cells), UCM‐MSC displayed a similar immunophenotype and similar multilineage differentiation ability, while demonstrating a higher expansion potential (average fold increase of 7.4 for serum‐containing culture medium and 11.0 for xeno‐free culture medium (P3‐P6)). The isolation and expansion of UCM‐MSC under defined serum‐/xeno‐free conditions contributes to safer and more effective MSC cellular products, boosting the usefulness of MSC in cellular therapy and tissue engineering.